Feeling in Crisis: Vicissitudes of Response in Experiments with Global Justice Education - Taylor, Lisa (Journal of the Canadian Association for Curriculum Studies, 2011)
<!--[if gte mso 9]> Normal.dotm 0 0 1 271 1545 York University 12 3 1897 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--StartFragment--> This paper considers the nexus of affective engagement, a critical analysis of systemic discrimination, and reflexive self-implication in education committed to social change. I ask how our inherited models and theories of learning and teaching for social change can curb our vigilance vis-à-vis the ways libidinal dynamics organize our curriculum as affective wish and our pedagogy as affective defense. I focus specifically on the qualities of global justice education—the ethical and political stakes of this project, the theories of learning, pedagogical strategies and discourses of moral development it inherits—that render learning, teaching, and learning to teach (none of which are discrete) affectively and ethically fraught. The paper examines student writing samples from a mandatory pre-service course on social and global justice education, one designed to engage future teachers in considering the inequitable global distribution of precarity and recognizability (Butler) within contemporary contexts of neoliberal globalization and war. In the writing samples, students reflect on the challenges they faced making sense of representations of the ravages of militarized capitalist globalization, in particular the challenges of creating and facilitating curriculum within which their peers might encounter such difficult knowledge. I ask, firstly, what students’ narrations of teaching social justice tell us about what is difficult in studying/teaching the devastation of the contemporary militarized, imperial global capitalist order in which we are profoundly implicated as citizens in the global North. Secondly, what can student narrations of teaching social justice tell me about what is difficult in global justice teacher education, specifically the wishes, the anxieties and discursive foreclosures underpinning my own conduct of it in this course? <!--EndFragment-->